2023
DOI: 10.1051/0004-6361/202245732
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of CH3CHCO in TMC-1 with the QUIJOTE line survey

Abstract: We report the detection of methyl ketene towards TMC-1 with the QUIJOTE line survey. Nineteen rotational transitions with rotational quantum numbers ranging from J = 3 up to J = 5 and Ka ≤ 2 were identified in the frequency range 32.0–50.4 GHz, 11 of which arise above the 3σ level. We derived a column density for CH3CHCO of N = 1.5 × 1011 cm−2 and a rotational temperature of 9 K. Hence, the abundance ratio between ketene and methyl ketene, CH2CO/CH3CHCO, is 93. This species is the second C3H4O isomer detected.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…On top of that, the N-and C-cyanomethanimine isomers do not emerge as the unique exception to the MEP, since recent detections in the ISM of many other isomeric families have also raised serious doubts about its general applicability regarding structural isomers. Some of these findings have demonstrated that high-energy structural isomers can share similar abundances to their more stable counterparts, as is the case for the H 2 CN and H 2 NC isomers (Cabezas et al 2021;Agúndez et al 2023a;San Andrés et al 2023) and the two most stable isomers within the C 3 H 4 O family (trans-propenal, CH 2 CHCHO, and methyl ketene, CH 3 CHCO; Bermúdez et al 2018;Fuentetaja et al 2023), or even higher, as noted for the C 3 H 2 O, C 2 H 4 O 2 , and C 2 H 5 N 2 O isomeric families (see, e.g., Loomis et al 2015 andShingledecker et al 2019;Mininni et al 2020;Rivilla et al 2023, respectively). Therefore, it is clear that the MEP cannot be taken as a strict rule to argue about the actual detectability of high-energy structural isomers in the ISM.…”
Section: High-energy Isomers In the Ismmentioning
confidence: 91%
“…On top of that, the N-and C-cyanomethanimine isomers do not emerge as the unique exception to the MEP, since recent detections in the ISM of many other isomeric families have also raised serious doubts about its general applicability regarding structural isomers. Some of these findings have demonstrated that high-energy structural isomers can share similar abundances to their more stable counterparts, as is the case for the H 2 CN and H 2 NC isomers (Cabezas et al 2021;Agúndez et al 2023a;San Andrés et al 2023) and the two most stable isomers within the C 3 H 4 O family (trans-propenal, CH 2 CHCHO, and methyl ketene, CH 3 CHCO; Bermúdez et al 2018;Fuentetaja et al 2023), or even higher, as noted for the C 3 H 2 O, C 2 H 4 O 2 , and C 2 H 5 N 2 O isomeric families (see, e.g., Loomis et al 2015 andShingledecker et al 2019;Mininni et al 2020;Rivilla et al 2023, respectively). Therefore, it is clear that the MEP cannot be taken as a strict rule to argue about the actual detectability of high-energy structural isomers in the ISM.…”
Section: High-energy Isomers In the Ismmentioning
confidence: 91%
“…A158, page 9 of 11 Maté, B., et al: A&A, 682, A158 (2024) Some COMs typical of hot cores and corinos such as C 2 H 3 CHO, C 2 H 3 OH, HCOOCH 3 , CH 3 OCH 3 , CH 3 CH 2 OH, CH 3 COCH 3 , CH 3 CH 2 CHO, and CH 3 CHCO have been found in TMC-1 (Agúndez et al 2021(Agúndez et al , 2023Fuentetaja et al 2023) which suggests a possible release of molecules to the gas phase from the surface of the grains. However, their abundances in TMC-1 are rather low compared with the carbon-bearing species formed in the gas-phase.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…space. 36 Prop-1-ene-1,1-diol ( 2) is the high energy tautomer of 3 but its preparation or spectroscopic data have not been reported. Enediol 2 is expected to form via a similar mechanism as demonstrated for the preparation of the enediol of acetic acid, which had been prepared only in 2020.…”
mentioning
confidence: 99%
“…35 Methylketene ( 4 , prop-1-en-1-one), which can also be considered as a precursor for the generation of 3 through the addition of water, has recently been detected in space. 36 Prop-1-ene-1,1-diol ( 2 ) is the high energy tautomer of 3 but its preparation or spectroscopic data have not been reported. Enediol 2 is expected to form via a similar mechanism as demonstrated for the preparation of the enediol of acetic acid, which had been prepared only in 2020.…”
mentioning
confidence: 99%